(3TQM eSGFd Mfjf Hf GSMGbs - (3CHh GdbGSe , YHO GdQMef Hf Ydj Hf CHi UGOb , GdfjSCHhQis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3GdaUd GdSGHY GdcdGe ai GdfHV(B: (3eG gh fHV GdYQhb GdVhGQH ,GdfHV gh MQcI ecGfjI jJMQcgG GdbdH s
(3BNQgG (B:s
(3cGf Gbhi ai JbhjI GdYVh hjfaY ef GdehGO GdeNJdaI Gdjg s
(3cJH HYV YfGhjfgG HGdNW Gdchai GdLejds
(3hHYV UaMGJgG MGFdg Gddhf HSHH GdQWhHI hjfbU hQbJjf ef GdfgGjgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs